Ruthenium‐Catalyzed meta‐CAr–H Bond Difluoroalkylation of 2‐Phenoxypyridines. Issue 13 (17th March 2020) - Jia, Chunqi; Wang, Shichong; Lv, Xulu; Li, Gang; Zhong, Lei; Zou, Lei; Cui, Xiuling
Abstract : A ruthenium‐catalyzed meta ‐selective CAr –H bond difluoroalkylation of 2‐phenoxypyridine using 2‐bromo‐2, 2‐difluoroacetate has been developed. Mechanistic studies indicated that this difluoroalkylation might involve a radical process. Furthermore, a new method is reported for the synthesis of 2‐( meta ‐difluoroalkylphenoxy)pyridine derivatives, which are present in many pharmaceuticals and other functional compounds. Abstract : A ruthenium‐catalyzed meta ‐selective CAr –H bond difluoroalkylation of 2‐phenoxypyridine using 2‐bromo‐2, 2‐difluoroacetate has been developed, which provide a new method to synthesize 2‐( meta ‐difluoroalkylphenoxy)pyridine derivatives, which are present in many pharmaceuticals and other functional compounds.